(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Tuberculosis is the ninth leading cause of death worldwide. India contributes to about one fifth of global TB burden. It is very important to diagnose early and treat Tuberculosis to cut down transmission of Tuberculosis. "Cartridge-Based Nucleic Acid Amplification Test (CBNAAT) plays a vital role in the rapid and accurate detection of Mycobacterium tuberculosis. Material and Methods: A retrospective, observational, record-based study conducted from March 2023 to February 2024 in Department of Microbiology. We included all patients who were subjected to CBNAAT and fluorescent microscopy for tuberculosis in the study period. Data was collected from CBNAAT centre, department of microbiology. We collected total number of samples regardless of age and tested for CBNAAT as well as smear microscopy for AFB. Results: A total of 1299 presumptive Tuberculosis cases were included in our study. Out of these, 143 (11%) patients were diagnosed as positive for TB in GeneXpert MTB/RIF assay in all age groups whereas AFB microscopy was positive in 41 (28.67%) cases. 102(71.33%) cases were missed by AFB microscopy which were MTB detected by molecular CBNAAT. Conclusion: CBNAAT is a highly sensitive molecular test that not only detects TB but also identifies rifampicin resistance within a short time, typically within two hours. CBNAAT is especially valuable in resource-limited settings due to its automation, minimal hands-on time, and applicability to various specimen types. By using this technique, we could detect the in the patients with the negative smear for microscopy.